PRODUCTION OF BIOGAS BASED ON HUMAN FESSES AS AN ALTERNATIVE ENERGY FOR REMOTE AREAS APPLICATION - Syofii, Imam; Sari, Dewi Puspita; Hermawan, Rudi (Indonesian Journal of Engineering and Science, 2022)
The utilise of biogas for remote areas is a problem because it is challenging to supply hydrogen. Hence a study of the utilisation of human fesses as biogas raw material for biogas production is proposed. Due to high investment costs to build miniature power plants, modified gasoline engines are used as mini power plants even though it is a laboratory scale. Based on results, human fesses can be used as raw material for biogas production. Performance engine using biogas derived from human fesses is 9% different from LPG. The maximum efficiency of the biogas system is 32%, and that of the LPG is 41%.